Development of Culture-Based Interactive Comic Media to Increase Students’ Mathematics Learning Motivation in Elementary Schools - Francisca, Yolla; Wahyudi , Wahyudi (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study developed a culture-based interactive comic media to increase motivation to learn mathematics in elementary schools. This media was designed to introduce Javanese culture and create more active and creative learning. The method used in this study was Research and Development (R&D) using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection was conducted through observation, interviews, and questionnaires at SD Negeri Sumberejo 01 with fourth-grade students as subjects. The results showed that the developed culture-based interactive comic was rated valid by experts, with scores ranging from